Heterogeneous microstructure evolution in Ti-6Al-4V alloy thin-wall components deposited by plasma arc additive manufacturing. (5th November 2018) - Lin, Jianjun; Guo, Dengji; Lv, Yaohui; Liu, Yuxin; Wu, Xiaoyu; Xu, Bin; Xu, Gang; Xu, Binshi
Abstract: Microstructural heterogeneity was observed in titanium alloys deposited by high-energy density beam additive manufacturing (AM) technologies in the as-built condition; these heterogeneities included the presence of coarse prior-β columnar grains, non-equilibrium layer bands(LBs), and mixed microstructures. This is particulary prominent with plasma arc AM (PAM), which has a higher heat input when compared to laser beam and electron beam AM technologies. In this study, several Ti-6Al-4V layers were deposited by PAM to investigate the characteristics of the generated microstructural heterogeneity. The results show that epitaxial growth of prior β columnar grains in the same direction is inhibited by pulsed perturbation, which results in formation of columnar grains with near-equiaxed grains. Horizontal LBs could be observed after depositing six layers. The phase transformation (β → α) followed the Burgers orientation relationship, resulting in triangular stars or rhombic patterns. Precipitation of secondary α nano dispersoids occurred along{10-10} orientation. The LB region of heterogeneity was affected by thermal cycles in the β-transus and the recrystallisation temperature ranges, which leads to α lamellae of the same orientation finally forming coarse α colonies, and dispersion strengthening of the α lamellae with α nano depersoids contributes to the microhardness. Graphical abstract: Several Ti-6Al-4V layers were deposited using pulsed plasma arc additive manufacturing (PAM). Epitaxial growth of prior β columnar grain is inhibited by pulsed perturbation, which results in formation of columnar grain with near-equiaxed grains. The horizonal layer bands (LBs) is observed after depositing 6 layers, which is absent in prior three layers. LB region deposited by PAM can be attributed to the precipitation of secondary α nano dispersoids growing along {10-10} orientation, which finally turn into α colonies under sufficient thermal cycles in the both range of β-transus and recrystallisation temperatures. Dispersion strengthening of the α lamellae with α nano contributes to an increase in the microhardness. The phase transformation (β → α) follows Burges oriention relationship resulting in triangular stars or rhombic patterns analysised by Electron Backscattered Diffraction. Unlabelled Image Highlights: Epitaxial growth of prior β-columnar grains is inhibited by pulsed perturbation. The horizonal layer bands (LBs) deposited result from sufficient thermal cycles in the both range of β- transus and recrystallisation temperatures. The heterogeneous microstructures follow the Burgers orientation relationship and coarse secondary α phase grows along {10-10} orientation. Dispersion strengthening of α lamellae with nano α contributes to an increase in the microhardness.